Women at a y-Walk party - Unknown:::Creator::::::::::::
Photograph shows a group of women sitting at a table socializing at a y-Walk party. Several of them are wearing y-Walk stickers and two of them are waving at the camera. They are probably at D.B. Cooper's and there are drinking glasses on the table and y-Walk balloon bouquets behind them.